Growth and trade - Maizels, Alfred; The National Institute of Economic and Social Research (London : Cambridge University Press, 1970)
This book analyses the long-term relationship between industrial growth and international trade in manufactured goods.
"Being an abbreviated version of Industrial growth and world trade."
Includes bibliographical references and index.
oo 12/11/2018
Loans
Keywords: Commerce; Industrialization